ANALISA ENERGI DAN EKSERGI PADA PENGERINGAN TEPUNG TAPIOKA MENGGUNAKAN PENGERING KONTINYU UNGGUN FLUIDISASI GETAR - Suherman Suherman; Rona Trisnaningtyas (Dept. of Chemical Engineering, Diponegoro University, 2016)
Energy and exergy analysis of cassava starch drying in continuous vibrated fluidized bed dryer were carried out to assess the performance of the system in terms of energy utilization ratio, energy efficiency, exergy inflow and outflow, exergy loss, and exergetic efficiency. The results showed cassava starch has starch content 87%, degree of whiteness 95%, negative fiber content, sperichal granula with average diameter12.32 μm, orthorhombic crystal structure and crystal size 47.467 nm . Energy utilization and energy utilization ratio increased from 0.08 to 0.20 J/s and 0.35 to 0.4 as the drying temperature increased from 50 to 70 oC. Energy efficiency increased from 13.80 % to 23.31 %, while exergy inflow, outflow, and losses increased from 4.701 to 14.678, 2.277 to 6.344, and 2.424 to 8.334 J/s respectively in the above temperature range. Exergetic efficiency decreased with increase in drying air temperature, while exergetic improvement potential increased with increased drying air temperature. Keywords: Cassava starch, continuous drying, energy and exergy analysis, vibrated fluidized bed Abstrak Analisis energi dan eksergi pengeringan pati tapioka menggunakan pengering kontinu unggun fluidisasi getar, telah dilakukan untuk menilai kinerja sistem dalam bentuk utilisasi energi, efisiensi energi, eksergi masuk dan keluar, eksergi hilang dan efisiensi eksergi. Hasil analisis pati memiliki kandungan starch 87%, tingkat keputihan 95%, kandungan serat negatif, bentuk partikel granular spherical dengan diameter 12,32 μm, struktur kristal orthorhombic dan ukuran kristal sebesar 47,467 nm. Peningkatan suhu pengering dari 50 menjadi 70 0C akan meningkatkan utilisasi energi dan rasio utilisasi energi dari 0,08 menjadi 0,20 J/s dan 0,35 menjadi 0,4. Efisiensi energi meningkat dari 13,80% hingga 23,31%, sedangkan eksergi masuk dan keluar, eksergi hilang meningkat dari 4,701 menjadi 14,678, 2,277 menjadi 6,344, dan 2,424 menjadi 8,334 J/s. Efisiensi eksergi menurun dengan naiknya suhu sedangkan potensi pengembangan eksergi meningkat dengan naiknya suhu. Kata kunci:. Analisis energi dan eksergi, pati tapioka, pengeringan kontinu, unggun fluidisasi getar